Religious responses to sex work and sex trafficking: an outrage against any decent people - McGrow, Lauren (Routledge studies in religion, 2023)
"This book examines the history, theological beliefs and current contextual practices of faith-based NGOs who work in the area of human trafficking involving the sex industry. There are hundreds of religious organizations around the globe who minister with human trafficking survivors and sex workers, but what is really happening on the ground and how do theological beliefs support a faith-based response? Many of these groups represent their work as a cosmic battle against evil forces, yet important structural critiques are elided in the urgency to rescue women and children. Using perspectives from both NGO staff and sex workers, an interdisciplinary panel of contributors examine specific organizations, highlight marginalized voices, and analyze undergirding methodologies. In doing so, the authors provide clear critiques and establish best practice guidelines for faith-based NGOs and future religious leaders, affirming an intersection of justice based upon critical reflection and careful action. This book addresses with nuance an important topic that is often over-simplified. It will, therefore, be of great interest to scholars studying the interaction of religion to sex work and human trafficking, as well as academics of Religious Studies and Theology more generally"--